2018
DOI: 10.1093/mnrasl/sly144
|View full text |Cite
|
Sign up to set email alerts
|

A sextet of clusters in the Vela OB2 region revealed by Gaia

Abstract: Using Gaia DR2 data, combined with OmegaCAM ground-based optical photometry from the AD-HOC survey, and detailed Radial Velocity measurements from ESO-Gaia, we analyse in detail a 10×5 deg region around the Wolf-Rayet star γ 2 Vel, including the previously known clusters Gamma Vel and NGC2547. Using clustering analysis that considers positions, proper motions and parallax, we discover 6 clusters or associations -4 of which appear new. Analysis of the colour-magnitude diagram for these clusters show that 4 of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…We utilize densitybased clustering (Ester et al 1996;Kriegel et al 2011) to the data set. It is a general statistical method that recently has begun to be applied to classify astronomical sources in a multidimensional data space (e.g., Beccari et al 2018Beccari et al , 2020Jerabkova et al 2019). This method can identify clusters in a multidimensional space not only for their crests but also for their spatial extent, without assuming that their underlying spatial structures are filamentary or clumpy.…”
Section: Appendix D Identification Of Emission Features Using Densitymentioning
confidence: 99%
“…We utilize densitybased clustering (Ester et al 1996;Kriegel et al 2011) to the data set. It is a general statistical method that recently has begun to be applied to classify astronomical sources in a multidimensional data space (e.g., Beccari et al 2018Beccari et al , 2020Jerabkova et al 2019). This method can identify clusters in a multidimensional space not only for their crests but also for their spatial extent, without assuming that their underlying spatial structures are filamentary or clumpy.…”
Section: Appendix D Identification Of Emission Features Using Densitymentioning
confidence: 99%
“…As mentioned previously, the Vela OB2 region has been recently the subject of several works aimed at studying the complexity of the stellar populations in the region. In Beccari et al (2018) we demonstrated that NGC 2457 and the cluster around the Wolf-Rayet Star γ 2 Vel belong to a complex constellation of sub-populations confined in a region of ∼100 pc 3 of volume. Later, Cantat-Gaudin et al (2019b) extended the study on a wider area of sky in a range of distances from ∼250 to ∼550 pc.…”
Section: Relic Stellar Filamentmentioning
confidence: 87%
“…Along this line, the Vela OB2 association has recently revealed to be one of the best test-bench to study the early stages of clustered star formation (SF) at ages 10 to 35 Myr. Using a combination of Gaia DR2 astrometric information and accurate photometry, Beccari et al (2018) recently studied a 10 × 5 deg region around the Wolf-Rayet Star γ 2 Vel, including the well known clusters Gamma Vel and NGC2547. They discovered an assembly of six clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Jeffries et al (2014) and Prisinzano et al (2016) estimate the mass of the cluster to be 100 M . Another cluster within the association, the P Puppis cluster, was identified by Caballero & Dinis (2008) and later by Beccari et al (2018).…”
Section: Structure and Agesmentioning
confidence: 99%